1999
DOI: 10.1042/0264-6021:3410655
|View full text |Cite
|
Sign up to set email alerts
|

Protein and gene structure of a blue laccase from Pleurotus ostreatus1

Abstract: A new laccase isoenzyme (POXA1b, where POX is phenol oxidase), produced by Pleurotus ostreatus in cultures supplemented with copper sulphate, has been purified and fully characterized. The main characteristics of this protein (molecular mass in native and denaturing conditions, pI and catalytic properties) are almost identical to the previously studied laccase POXA1w. However, POXA1b contains four copper atoms per molecule instead of one copper, two zinc and one iron atom per molecule of POXA1w. Furthermore, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 10 publications
3
98
0
3
Order By: Relevance
“…Peniophora sp was the best laccase producer under this condition (4140 U/L), but G. applanatum was particularly sensitive to the addition of copper, increasing the production (1850 U/L) in the presence of copper. Our results agree with those of Giardina et al (1999), who observed that P. ostreatus produced a significantly greater amount of laccase (30,000 U/L) in nitrogen-rich medium and in the presence of 150 mM CuSO 4 compared to that produced in the absence of copper (4000 U/L). Shutova et al (2008) used higher CuSO 4 concentrations than those used in our study (1500-2000 mM) and observed positive effects on laccase activity in Lentinus tigrinus (47,000 U/L).…”
Section: Laccase Production In Liquid Medium Containing Different Consupporting
confidence: 83%
“…Peniophora sp was the best laccase producer under this condition (4140 U/L), but G. applanatum was particularly sensitive to the addition of copper, increasing the production (1850 U/L) in the presence of copper. Our results agree with those of Giardina et al (1999), who observed that P. ostreatus produced a significantly greater amount of laccase (30,000 U/L) in nitrogen-rich medium and in the presence of 150 mM CuSO 4 compared to that produced in the absence of copper (4000 U/L). Shutova et al (2008) used higher CuSO 4 concentrations than those used in our study (1500-2000 mM) and observed positive effects on laccase activity in Lentinus tigrinus (47,000 U/L).…”
Section: Laccase Production In Liquid Medium Containing Different Consupporting
confidence: 83%
“…Varied Lac isoenzyme patterns of fungal origin are obtainable according to the culture conditions used, and this enzymatic potential becomes relevant for the efficient colonization of the substrate and growth (Das et al 1997;Giardina et al 1999). Both ND-PAGE and PAGE methods applied in this work revealed the existence of isoenzymes of different MWs appearing at different conditions of pH and temperature.…”
Section: Resultsmentioning
confidence: 92%
“…The existence of multiple genes encoding different laccase isoenzymes has been demonstrated in several fungi (Mansur et al, 1997;Smith et al, 1998;Giardina et al, 1999). Moreover, laccase gene expression depends on cultural conditions, and differentially regulated systems to control laccase production have been reported (Collins & Dobson, 1997;Mansur et al 1998;Muñoz et al;.…”
Section: Introductionmentioning
confidence: 99%
“…Pleurotus ostreatus is a basidiomycete that secretes several laccase isoenzymes, four of which, named POXC (Giardina et al, 1996), POXA1w (Palmieri et al, 1997), POXA3 and POXA1b (Giardina et al, 1999), have been purified and characterized. Four different P. ostreatus laccase genes and their corresponding cDNAs have been cloned and sequenced: poxc (Giardina et al, 1996) (previously named pox2), poxa1b (Giardina et al, 1999), poxa3 (Gene Bank accession no.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation